Politik Kekerabatan dalam Pelaksanaan Pemerintahan Desa Tanjung Pauh Mudik - Bobbi Noptin Anggra; Suryanef Suryanef (PERSPEKTIF, 2022)
The purpose of this research is to examine the implementation of kinship politics, community response, implications and filling in the membership of the Tanjung Pauh Mudik Village BPD political practice in village head elections. The problem is focused on kinship politics. To approach this problem, a theoretical reference from Pablo Querobin (2011) is used which states that dynastic politics is a special form of elite efforts to maintain power in which one or several family groups monopolize political power. The data were collected through direct interviews to the field and analyzed qualitatively. This study concludes that the political implementation of Tanjung Pauh Mudik Village is based on the urgent interests of someone who is running as a candidate for village head and a member of the local village BPD. The community's response to the politics of kinship that occurred in the village of Tanjung Pauh mudik is very visible in the concept of applying the norms that tend to be seen in the village. In the kinship politics in Tanjung Pauh Mudik Village, it has been seen that there is continuity between people who use kinship politics as a reference to get positions easily.